Early sunshine duration and cloud cover records in Coimbra (Portugal) for the period 1891–1950. (2nd April 2021) - Montero‐Martín, Javier; Antón, Manuel; Vaquero, José Manuel; Neto, Jorge; Sanchez‐Lorenzo, Arturo
Abstract: The recovery of early sunshine duration (SD) records is crucial to improve knowledge of the long‐term evolution of incoming solar radiation at the Earth's surface. This work analyses daily SD data digitized from the Meteorological Observatory of Coimbra (Portugal) during 1891–1950. The Coimbra SD records are the earliest series in Portugal and the second one in the whole Iberian Peninsula (i.e., the first being in Madrid, Spain). The analysis shows that SD time series is homogenous except for a break in 1937–1938, which may be likely related to a change of the SD recorder (i.e., Jordan device replaced by a Campbell‐Stokes recorder). Once the temporal inhomogeneity has been corrected, a slightly negative trend of −0.09 ± 0.06 hr per decade is found for the whole 1891–1950 period. It must be highlighted the marked decrease in SD records of −0.51 ± 0.32 hr per decade observed from the beginning of the time series until the 1910s ('early dimming') in line with other studies available in the literature. Both trends (whole and 'early dimming' periods) are statistically significant at the 95% confidence level. By contrast, from 1920s until 1950 no statistically significant long‐term changes in SD records are found. Additionally, cloud cover data in Coimbra have been also digitized and analysed for the common period. A positive statistically significant trend of 0.13 ± 0.06 tenths per decade is found for the 1891–1950 period which may explain the negative trend of SD records in this same period. Nevertheless, the analysis of SD long‐term trends under cloudless conditions suggests that other atmospheric factors such as the aerosol load could likely also play a relevant role on the SD evolution. The SD and cloud cover data from 1891 to 1950 is made available for the scientific community in digital form. Abstract : Coimbra time series of SD records are at present the earliest series in Portugal. An early dimming is observed during 1891–1913 followed by a stable period until 1950. There is a positive trend in the homogeneous Cloud Cover time series during 1891–1950.